2015
DOI: 10.5688/ajpe79691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Flexible Learning about Aseptic Compounding on First-year Students in a Pharmacy Skills Laboratory

Abstract: Objective. To evaluate how flexible learning via online video review affects the ability and confidence of first-year (P1) pharmacy students to accurately compound aseptic preparations. Design. Customary instructions and assignments for aseptic compounding were provided to students, who were given unlimited access to 5 short review videos in addition to customary instruction. Student self-confidence was assessed online, and faculty members evaluated students' aseptic technique at the conclusion of the semester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, these improvements did not increase the students' performance on either of the two non-sterile lab practicals. Such a lack of affect may be attributed to the fact that the mean score for each of these assessments was already relatively high (Neville et al, 2015). It should also be noted that the modifications made to the pre-lab assignments and the corresponding group discussions did not deteriorate student performance either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these improvements did not increase the students' performance on either of the two non-sterile lab practicals. Such a lack of affect may be attributed to the fact that the mean score for each of these assessments was already relatively high (Neville et al, 2015). It should also be noted that the modifications made to the pre-lab assignments and the corresponding group discussions did not deteriorate student performance either.…”
Section: Discussionmentioning
confidence: 99%
“…This mindset became particularly evident as the routine of the labs was established and the students' exam schedules began. Such a mindset might be indicative of a learner who simply desires more flexibility to learn on their own schedule and at their own pace (Neville et al, 2015;Kratochwill et al, 2016), but may also be indicative of a leaner who is trying to minimise their effort by simply getting the answers from the keys provided after each lab. In either case, this also placed extra burdens upon the lab instructors, who needed to regularly field student requests to leave prior to the completion of the application questions, deal with irate or annoyed students, and police students who were trying to sneak out of the lab.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike traditional learning environments, which typically require students to follow a linear sequence, online environments allow learners to follow a more individualized approach: viewing the instructional material in a sequence that best meets their needs, repeating or skipping sections, and following subjects regardless of the order in which they have been arranged (Hung et al, 2010). Moreover, audio and video formats enable students to control the pace at which they consume and review content (Neville et al, 2015). Flexibility regarding content may range from being completely open, where the learner is making all the choices, to providing options within a particular framework established by the instructor (Hill, 2006).…”
Section: Flexible Learning In Online Coursesmentioning
confidence: 99%
“…Others choose online courses in order to reduce the number of times they have to travel to campus. Jaggars (2014) reported that students appreciate the comfort of working at home (e.g., taking breaks, having snacks), and some feel that instructional materials in a flexible format offer them more control while still supporting course outcomes (Neville et al, 2015).…”
Section: Flexible Learning In Online Coursesmentioning
confidence: 99%
“…Skills laboratories are a fundamental component of pharmacy curricula and are a place where students engage in activities that allow them to apply learned concepts and test their knowledge. [2][3][4][5] Skills laboratory faculty design and develop experiences based on ACPE standards to ensure that students possess the basic knowledge, skills, and abilities to independently practice pharmacy at the time of graduation. While the ACPE standards are useful, they do not clearly outline the essential skills needed to be taught and assessed in a skills laboratory setting in order to best prepare practice ready graduates.…”
Section: Introductionmentioning
confidence: 99%